Drug Effects : Khat in Biocultural and Socioeconomic Perspective. - Gezon, Lisa (Advances in critical medical anthropology, 2012)
Khat, marijuana, peyote - are these dangerous drugs or vilified plants with rich cultural and medical values? In this book, Lisa Gezon brings the drug debate into the 21st century, proposing criteria for evaluating psychotropic substances. Focusing on khat, whose bushy leaves are an increasingly popular stimulant and the target of vehement anti-drug campaigns, she explores biocultural and socioeconomic contexts on local, national, and global levels. Gezon provides a multi-disciplinary examination of the plant's direct physical and psychological effects, as well as indirect social and.